South Asia and European Integration - Lessons from the Past and Future Prospects (The Distinguishedl Lecture) (The Pakistan Development Review, 1989)
During its more than 30 years of existence, the European Economic Community has developed from a relatively loose association of a handful of countries which had just overcome the worst after-effects of the second world war to become the most powerful economic block consisting of 12 countries which represent less than 10 percent of the world's population, but about 28 percent of production and 38 percent of world trade (including trade among member countries). With the further dismantling of internal barriers to trade flows and factor migration by 1992, the Community is expected to further increase its economic might and thereby to become more and more attractive for other countries to apply for membership. TIlis raises the question how countries which are outside and are likely to remain outside the Community will be affected by such a development. The question has an economic as well as a political dimension. I will focus here on the first, but also make a few remarks on the latter.